127 NOVEL ROLE OF INFLAMMATORY FACTOR NUCLEAR FACTOR κB DURING MOUSE LUNG EMBRYOGENESIS. Issue 1 (1st January 2007) - Londhe, V. A.; Nguyen, H. T.; Li, X.; Li, C.; Zhu, N. L.; Minoo, P.
Abstract : Background: The consequence of inflammation superimposed upon immature lungs leads to developmental lung abnormalities such as bronchopulmonary dysplasia (BPD). BPD continues to have an incidence of 30% among premature newborns despite significant advances in neonatal care. The morphoregulatory molecules that drive lung development include transcription factors, signaling molecules, and extracellular matrix (ECM) proteins and receptors. Nuclear factor κB (NF-κB) is a transcription factor central to multiple inflammatory signaling pathways. Recently, a new role for NF-κB has been described in mammalian limb and mammary gland morphogenesis as well as in lung branching in chick lung embryo. There is currently little to no information regarding the role of NF-κB in mammalian lung development. Objectives: To determine the role of NF-κB during mouse lung embryogenesis by (1) characterizing NF-κB expression pattern in wild-type mice and (2) generating hypermorphic transgenic mice for NF-κB to determine the phenotypic impact of NF-κB overexpression. Design/Methods: Pregnant wild-type C57BL/6 mice and newborn pups were sacrificed to obtain fetal lungs at designated gestational ages ranging between E12 and E18 for mRNA and protein analysis of NF-κB. A transgenic mouse line was generated by first subcloning human NF-κB (p65) cDNA into a SpC-promoter-driven expression vector followed by subsequent injection into single- to two-staged mouse embryos and reimplantation into pseudopregnant female mice. The offspring were genotyped to establish expression of the NF-κB transgene and lungs were harvested for mRNA, protein, and histologic analysis. Results: NF-κB mRNA expression in the developing lung is maximal between E12 to E15 and decreases to minimal levels from E18 through adulthood. Transgenic mice overexpressing NF-κB in type II alveolar precursor cells demonstrated increased NF-κB mRNA levels via Northern blot and increased protein expression via immunohistochemical analysis compared with wild-type controls. Importantly, overexpression led to phenotypic changes characterized by a paucity of airspaces. Finally, immunohistochemical analysis revealed an increase in markers for alveolar type II cells. Conclusions: The phenotypic changes due to overexpression of NF-κB in the developing mouse lung suggest that NF-κB may play an important role during lung morphogenesis and subsequently during lung injury and repair. The molecular signals regulating NF-κB expression remain to be elucidated.